Dynamic Factor Price Equalization and International Income Convergence - Shiells, Clinton; Francois, Joseph (Washington, D.C. : International Monetary Fund, 2008)
The paper develops a tractable way to incorporate the micro structure of dual models of international trade into a standard class of dynamic open-economy macro models. In the process, it develops the concept of a dynamic factor price equalization set and an integrated intertemporal equilibrium. A number of results are obtained concerning trade, growth, and income convergence. Countries with higher capital/labor ratios may stay wealthier over time, both in the transition and in the new steady state. Real shocks in one country will be transmitted to the other country through the factor markets and traded goods prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet